2012
DOI: 10.1029/2011jd016603
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent effects on the microphysics and initiation of warm rain in deep convective clouds: 2‐D simulations by a spectral mixed‐phase microphysics cloud model

Abstract: [1] The spectral bin microphysics Hebrew University cloud model with the spatial resolution of 50 Â 50 m is used to simulate the evolution of isolated deep mixed phase convective clouds under different meteorological conditions and at different aerosol concentrations. The model takes into account the effects of turbulence on droplet collision rate. Turbulent collision kernels are calculated at each time step and at each grid point. The turbulence-induced collision rate enhancement is determined by means of loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 147 publications
3
76
0
Order By: Relevance
“…This potential longevity may affect the aerosols' radiative effect and its prolonged involvement in ice nucleation, cloud activation, and precipitation. The particle density decrease may also change how an aerosol affects turbulence in a cloud, further influencing cloud development and precipitation (52). Moreover, the particles' larger and corrugated surface area may increase gas adsorption and rates of light-induced heterogeneous chemical processes (53).…”
Section: Discussionmentioning
confidence: 99%
“…This potential longevity may affect the aerosols' radiative effect and its prolonged involvement in ice nucleation, cloud activation, and precipitation. The particle density decrease may also change how an aerosol affects turbulence in a cloud, further influencing cloud development and precipitation (52). Moreover, the particles' larger and corrugated surface area may increase gas adsorption and rates of light-induced heterogeneous chemical processes (53).…”
Section: Discussionmentioning
confidence: 99%
“…This choice of threshold is motivated by the recognition that a characteristic or critical droplet radius exists, above which intense droplet coalescence triggers rapid drizzle formation. This radius is found to be 12-14 µm as shown by satellite and ground-based observations (Suzuki et al, 2010;Rosenfeld, 2000;Rosenfeld and Gutman, 1994), aircraft measurements (Gerber, 1996;Boers et al, 1998;Freud and Rosenfeld, 2012), and numerical simulations (Magaritz et al, 2009;Pinsky and Khain, 2002;Benmoshe et al, 2012). This retrieval technique allows us to retrieve not only drizzle microphysical properties below the cloud base but also within the cloud at the same time.…”
Section: Introductionmentioning
confidence: 94%
“…[], the values of ε in deep cumulus clouds may range from several hundred cm 2 s − 3 to ~ 2 ⋅ 10 3 cm 2 s − 3 . Simulations of mixed‐phase deep convective clouds performed by Benmoshe et al [] using the Hebrew University cloud model (HUCM) supported the validity of these estimations. It was shown that the intensity of turbulence is distributed over the cloud in a highly inhomogeneous manner, indicating the presence of so‐called large‐scale turbulence intermittency.…”
Section: Introductionmentioning
confidence: 99%
“…Under such intense turbulence, collision kernels can exceed gravitational kernels by a factor as high as 5–15 [ Pinsky et al , ]. Benmoshe et al [] investigated the role of turbulence in formation of first raindrops in deep convective clouds under different aerosol loadings. The values of ε and Re λ were calculated at each model grid point using the equation for turbulence kinetic energy, as well as some assumptions concerning the maximum scales of turbulent vortices following from the theory of cloud top entrainment instability proposed by Grabowski and Clark [, ].…”
Section: Introductionmentioning
confidence: 99%